Ciclo vital da família: Reflexão sobre as especificidades étnicas e culturais do desenvolvimento das famílias africanas - Simões, Tchilissila Alicerces (2017)
Family psychology has emphasized the role of ethnic and cultural specifics in family development and functioning. However, little is known about how African (sub-Saharan) families function over the course of their development. This paper aims to identify in which way the theoretical models and empirical studies characterise the development and functioning (in terms of stress/tension, strengths, rituals and routines) of African families during their life cycle. The existing theory was revised based on bibliographic research, leading to the analysis of 22 articles. The results illustrate a lack of research focused on African families. The researches mentioned in the analysed articles show that there are specific issues related to triggering situations of stress/tension and strengths within African families, as well as the stabilizing and organizational role of rituals and routines during transitional times. From the theoretical revision emerged the need to create models of family development that are adjusted to the ethnic and cultural specificities of these families, as well as to promote further research into its functioning, so as to create a thorough theoretical framework that can be applied to evaluate and intervene on a family level.